The Effect of Service Quality, Product Reviews, Risk Perception, and Usability Perception on Online Food Purchasing Decisions - Salsabilla, Sally; Hidayati, Lukluk Atul; Santosa, Mulato (International Journal Labs, 2023)
This study was conducted to examine and analyze the effect of Service Quality on Purchase Decisions, the effect of Product Reviews on Purchase Decisions, the impact of Risk Perception on Purchase Decisions, and the development of Perceived Ease on Purchase Decisions. The sample in this study were students of the Faculty of Economics and Business, University of Muhamadiyah Magelang, which had 100 students. The sampling method in this study was purposive sampling. The analytical tool in this study uses multiple regression analysis with SPSS 25.0. The results showed that Service Quality, Product Reviews, and Perceptions of Ease did not positively or significantly affect online food purchasing decisions. In contrast, Risk Perceptions significantly impacted online food purchasing decisions.